Bacterial endocarditis in subjects 60 years of age and older - Thell, R; Martin, F H; Edwards, J E (Circulation (New York, N.Y.), 1975)
Forty-two cases of bacterial endocarditis with pathologic confirmation are reviewed. Infection was restricted to one or both left-sided valves in 31 cases, right-sided valves in five cases, and valves in both sides of the heart in six cases. In those specimens available for review, underlying valvular disease was identifiable in 24 of 38 cases (63%). The common underlying diseases, in order of decreasing frequency, were calcified or otherwise deformed aortic valves (11 cases) and rheumatic fibrosis of the mitral valve (eight cases). The floppy mitral valve was the underlying condition in two cases and amyloid infiltration of the tricuspid valve in one. Among the 34 cases from which a specific organism was identified, the dominant organisms were Staphylococcus (14 cases) and various types of Streptococci(ten cases). Fungi were the causative organisms in two cases. The clinical suspicion for the presence of bacterial endocarditis was low (40% of 40 cases with adequate data). In those cases with adequate data, murmurs were present in 68% and fever in 93%. Of those patients with fever, clinical diagnosis was made or suspected in only 38%. When a murmur was present, the clinical diagnosis was made or suspected in 54% of the cases, while when a murmur was absent the disease was suspected in only 9% of the cases. The clinical diagnosis of bacterial endocarditis in older subjects depends upon 1) knowledge that the disease may occur in such subjects and 2) recognition that, although fever is commonly present, murmurs may be absent.